A discussion of the Muscle Tuning and the Preferred Movement Path concepts - comment on Nigg et al. - Peter Federolf; Aude-Clémence M. Doix; Daniel Jochum (Bern Open Publishing, 2018)
Nigg and colleagues propose two new paradigms, the Muscle Tuning and the Preferred Movement Path concepts. The purpose of this commentary is to discuss plausibility and challenges of these two concepts. Both concepts are highly plausible from a mechanical point of view and they also go in line with every-day observations. The main challenges for the muscle tuning paradigm are that (a) this mechanism is only one of several mechanisms in how the body adapts to impacts, and (b) it is very difficult to develop testable predictions from this paradigm since the mechanical (vibrational) properties of the leg are highly subject-specific and complex. The main open questions regarding the preferred movement path paradigm relate to (a) its integration with the concepts for movement variability, and (b) to the circumstances under which the preferred movement path might change.